The identification and characterization of glycoproteins observed in potatoes following Fusarium solani infection - Strydom, Susanna M.(Susanna Magdalena) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1992.